THE EFFECT OF TRANSFORMATIONAL LEADERSHIP, INTERPERSONAL COMMUNICATION AND WORK STRESS ON EMPLOYEE PERFORMANCE AT PT FEDERAL INTERNATIONAL FINANCE, SUKABUMI CITY - Rozan Vina Rahmani; Hesri Mintawati; Slamet Sutrisno (RADJA PUBLIKA, 2025)
This study aims to determine how much influence transformational leadership interpersonal communication and work stress have on employee performance at PT FIFGROUP, Karang Tengah District, Gunung Puyuh Village, Sukabumi City. The research method used in this study is quantitative descriptive through a survey using a data collection tool in the form of a questionnaire that has previously been tested for validity and reliability of the instrument so that the target population is PT FIFGROUP employees through classical assumption tests, validity tests, reliability tests, homogeneity tests, heteroscedasticity tests and autocorrelation tests on each variable. The data analysis technique used is simple and multiple regression analysis before data analysis is carried out, requirements testing is first carried out.